The Role of the Endophytic Microbiome in the Grapevine Response to Environmental Triggers - Pacifico, Davide; Squartini, Andrea; Crucitti, Dalila; Barizza, Elisabetta; Lo Schiavo, Fiorella; Muresu, Rosella; Carimi, Francesco; Zottini, Michela (Frontiers in Plant Science, 2019)
Endophytism within Vitis represents a topic of critical relevance due to the multiple standpoints from which it can be approached and considered. From the biological and botanical perspectives, the interaction between microorganisms and perennial woody plants falls within the category of stable relationships from which the plants can benefit in multiple ways. The life cycle of the host ensures persistence in all seasons, repeated chances of contact and consequent microbiota accumulation over time, leading to potentially high diversity compared with that of herbaceous short-lived plants. Furthermore, grapevines are agriculturally exploited, highly selected germplasms where a profound man-driven footprint has indirectly and unconsciously shaped the inner microbiota through centuries of cultivation and breeding. Moreover, since endophyte metabolism can contribute to that of the plant host and its fruits’ biochemical composition, the nature of grapevine endophytic taxa identities, ecological attitudes, potential toxicity, and clinical relevance are aspects worthy of a thorough investigation. Can endophytic taxa efficiently defend grapevines by acting against pests or confer enough fitness to the plants to endure attacks? What are the underlying mechanisms that translate into this or other advantages in the hosting plant? Can endophytes partially redirect plant metabolism and to what extent do they act by releasing active products? Is the inner microbial colonization necessary priming for a cascade of actions? Are there defined environmental conditions that can trigger the unleashing of key microbial phenotypes? What is the environmental role in providing the ground biodiversity by which the plant can recruit microsymbionts? How much and by what practices and strategies can these symbioses be managed, applied and directed to achieve the goal of a better sustainable viticulture? By thoroughly reviewing the available literature in the field and critically examining the data and perspectives, the above issues are discussed.